Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen : (Studi pada salah satu perusahaan jasa transportasi di Kota Bandung) - Aditia Aditia; Anton Tirta Komara; Nita Yura Roslina; Lungguh Jatmika (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
This study aims to determine service quality and price on customer satisfaction. The research method used is a survey method on 100 customers at one of the transportation service providers in the city of Bandung. The path analysis technique is used to answer the problem formulation. The results show that the service quality variable and the price variable have a significant effect either partially or simultaneously on customer satisfaction; however, there are still several factors that influence customer satisfaction outside of this study. The study results recommend that the company's management provide directives and strict rules to bus officers always to pay attention and make time-efficient, for example, the time of bus departure and bus arrival on the destination route so that there are no delays.